ANALISIS KONFLIK TOKOH UTAMA DALAM NOVEL DIARY ISTRI SEORANG PELAUT KARYA RENI RIMBAFANI - Hartina Suriyani; Antonius Totok Priyadi; Sesilia Seli (Universitas Tanjungpura, 2019)
AbstractThis study was the Diary of the Wife of A Sailor's Wife by Reni Rimbafani, while the data were internal conflicts and external conflicts in the form of quotes, phrases, sentences or paragraphs.Based on the results of the analysis and regarding internal conflicts and external conflicts, internal conflicts of the main characters of Reni include; feeling angry, disappointed, upset, sorry, anxious, hurt, sad. Analysis is done by looking at internal conflicts experienced by the main characters based on behavioristic psychological approaches. Reni's external conflict includes physical conflict and social conflict. Physical conflicts experienced by Reni include; Reni and Haiyan Typhoon, Reni and Heavy Rain. The social conflict experienced by Reni was a fight between Reni and her husband. Plans for implementing novel learning in schools can use the STAD type cooperative model, question and answer method, discussion and assignment, visual media, evaluasi in the form of description test and oral test. Keywords: conflict. main character, novel